Business - Pride, William M.; Hughes, Robert J.; Kapoor, Jack R. (Boston : Houghton Mifflin Co., 1988)
The second edition of this book covers new topics, presents expanded coverage of important issues.
Part 1. American business today -- Part 2. Management and organization -- Part 3. The human resource -- Part 4. Marketing -- Part 5. Finance and investment -- Part 6. Information for business -- Part 7. The business environment.
Includes bibliographical references and index.
Keywords: BUSINESS MANAGEMENT; BUSINESS ENTERPRISE